2017
DOI: 10.1109/twc.2016.2646682
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging the Near–Far Effect for Improved Spatial-Reuse Scheduling in Underwater Acoustic Networks

Abstract: We present a spatial reuse resource allocation scheme for underwater acoustic networks that organizes communications so as to avoid destructive collisions. One prime source of collisions in underwater acoustic networks is the so called near-far effect, where a node located farther from the receiver is jammed by a closer node. While common practice considers such situation as a challenge, in this paper we consider it as a resource, and use it to increase the network throughput of spatial reuse time-division mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…In [21], showed that channel shared among contending sensor device to utilize resource efficiently. However, sharing channel are prone to impersonation and various other kind of attacks [22].…”
Section: Litterature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…In [21], showed that channel shared among contending sensor device to utilize resource efficiently. However, sharing channel are prone to impersonation and various other kind of attacks [22].…”
Section: Litterature Surveymentioning
confidence: 99%
“…However, sharing channel are prone to impersonation and various other kind of attacks [22]. In [21] presented a spatial reuse based resource allocation model for UWSN for avoiding destructive collision. Major cause of such collision is due to near-far effect [18] where sensor device placed faraway from receiver is jammed by a closer sensor device.…”
Section: Litterature Surveymentioning
confidence: 99%
“…To increase the network throughput of spatial reuse, Diamant et al [29] leveraged the near-far effect caused by large propagation delay in UANs and proposed a near-far spatial reuse TDMA (NF-TDMA) algorithm for both contention-free and opportunistic transmissions. The proposed NF-TDMA represents a combination of centralized schedule and distributed schedule used to obtain an optimal channel utilization for a given interference cancellation capability of the system that can opportunistically utilize the information on occurrences of near-far scenarios in UANs to maximize the channel utilization.…”
Section: Related Workmentioning
confidence: 99%
“…We divided the simulation into two parts. In the first part, we validated the MLOPS algorithm, and in the second part, we compared the MLOPS with the traditional TDMA and NF-TDMA protocols [29].…”
Section: Simulationmentioning
confidence: 99%
“…It is urgent to develop a near field communication mode with stronger compatibility, lower cost and more convenient management to realize the fast response of vehicle terminal.Acoustic wave communication is a kind of near field communication mode, which transmits information by acoustic wave [19]. However, the study of acoustic communication started late, the related technology rarely reported, mainly concentrated on the field of underwater acoustic communications [20][21][22][23]. In 1945, the first underwater acoustic communication system was developed by the US Navy's underwater acoustic laboratory, which was mainly used for communication between submarines.…”
mentioning
confidence: 99%